Nrf2 Mitigates RANKL and M-CSF Induced Osteoclast Differentiation via ROS-Dependent Mechanisms - Yang Yang; Zhiyuan Liu; Jinzhi Wu; Simeng Bao; Yanshuai Wang; Jiliang Li; Tao Song; Yongxin Sun; Jingbo Pi (MDPI AG, 2023)
Nuclear factor-erythroid 2-related factor 2 (Nrf2) has been shown to be a negative regulator of osteoclast differentiation, but the precise mechanisms have not yet been established. We examined the precise roles of Nrf2 in regulating antioxidants and reactive oxygen species (ROS) levels, especially the cytoplasmic and mitochondrial ROS during osteoclastogenesis in vitro. In the current study, we found that the absence of Nrf2 promotes osteoclast differentiation in bone-marrow-derived macrophages (BMMs) and RAW 264.7 cells. The receptor activator of NF-κB ligand (RANKL) and macrophage colony-stimulating factor (M-CSF) significantly lowered the levels of Nrf2 and its downstream antioxidant enzymes at mRNA and/or protein levels during osteoclast differentiation in the BMMs of mice and RAW 264.7 mouse leukemic monocytes. Compared to the wild-type cells, Nrf2-deficient cells exhibited heightened sensitivity to both transient RANKL-induced cytoplasmic ROS and prolonged RANKL and M-CSF-induced cytoplasmic and mitochondrial ROS accumulation. Furthermore, exogenous antioxidant agents, including N-acetyl-cysteine (NAC), diphenyleneiodonium chloride (DPI), and mitoquinone mesylate (MitoQ), exhibited substantial capability to suppress the elevation of ROS levels during osteoclast differentiation induced by Nrf2 deficiency, and they consequently inhibited osteoclast differentiation augmented by the lack of Nrf2. The activation of phosphorylated c-FOS resulting from elevated ROS promoted osteoclast differentiation. The inhibition of c-FOS blocked osteoclast differentiation, which was elevated by Nrf2-deficiency. Taken together, these data reveal that Nrf2 effectively decreased the accumulation of intracellular ROS and the phosphorylation of c-FOS during osteoclastic differentiation by regulating antioxidant enzymes and subsequently inhibited RANKL-induced osteoclast differentiation.